BiFeO3/TiO2 nanotube arrays composite electrode: Construction, characterization, and enhanced photoelectrochemical properties - Zhu, A.; Zhao, Q.; Li, Xin Yong; Shi, Y. (2014)
This work aims at the exploration of nanostructured ferroelectric-material-modified semiconductor electrodes for enhanced photo-induced activity. A well-aligned BiFeO3/TiO2-nanotubes (NTs) array with visible-light activity was successfully synthesized on a titanium sheet by combining anodization and an ultrasonic-immersion method followed by annealing. The structural and optical properties of the TiO2-NTs and the composite BiFeO3/TiO2-NTs were comparatively characterized. The composite BiFeO3/TiO2-NTs grown on a Ti sheet and used as an electrode exhibited a stronger absorption in the visible region and a much higher photoconversion efficiency than the pure TiO2-NTs/Ti electrode. Electrochemical impedance investigation attested to a significant improvement of the interfacial electron-transfer kinetics with enhanced separation of electron-hole pairs. The as-prepared composite electrode showed a high efficiency for photoelectrocatalytic degradation towards rhodamine B under visible-light irradiation (λ > 400 nm). The enhanced photoelectrocatalytic activity of the composite electrode could be attributed to the synergistic effect between the lowered electron-hole recombination rate by the applied bias and the wider spectral response promoted by the BiFeO3 component.